2019
DOI: 10.1186/s12889-019-6939-2
|View full text |Cite
|
Sign up to set email alerts
|

Child friendly spaces impact across five humanitarian settings: a meta-analysis

Abstract: Background Humanitarian crises present major threats to the wellbeing of children. These threats include risks of violence, abduction and abuse, emotional distress and the disruption of development. Humanitarian response efforts frequently address these threats through psychosocial programming. Systematic reviews have demonstrated the weak evidence-base regarding the impact of such interventions. This analysis assesses the impact of Child Friendly Spaces (CFS), one such commonly implemented interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 16 publications
2
24
0
1
Order By: Relevance
“…Findings showed variation in benefits across sites and outcomes. Analyses support earlier findings [ 28 ] of small to moderate impacts on psychosocial wellbeing indicators after participation in CFS [ 29 ]. However, with improved well-being amongst comparison populations over time, these intervention benefits were generally not evident at 1-year follow-up.…”
Section: Initial Findingssupporting
confidence: 83%
See 1 more Smart Citation
“…Findings showed variation in benefits across sites and outcomes. Analyses support earlier findings [ 28 ] of small to moderate impacts on psychosocial wellbeing indicators after participation in CFS [ 29 ]. However, with improved well-being amongst comparison populations over time, these intervention benefits were generally not evident at 1-year follow-up.…”
Section: Initial Findingssupporting
confidence: 83%
“…De Jong, Ager and coworkers conducted an evaluation of psychological first aid as applied in the Ebola crisis in Liberia and Sierra Leone [ 27 ]. Savage and colleagues evaluated child friendly spaces across crises in Jordan, Nepal and Uganda [ 28 , 29 ], and are now conducting a trial of an enhanced CFS-design in Uganda.…”
Section: R2hc-funded Mhpss Researchmentioning
confidence: 99%
“…The field of mental health and psychosocial support (MHPSS) is poised to consolidate robust evidence on what works in humanitarian settings; specifically, it must assess why program impacts (often measured using self, parent, or teacher reports) are mostly small, variable, or nil, especially over the long-term [17]. Psychosocial interventions for children and adolescents are one of the most frequently implemented, yet poorly evaluated, interventions in crisis settings [1,18,19]. This proves frustrating for humanitarians looking for credible, actionable evidence in MHPSS programming.…”
Section: Scientific Importancementioning
confidence: 99%
“…The representatives from the NGOs said that they did not have the staff to take care of traumatized children, and they pointed to a need for capacity building. Although they had started up child-friendly spaces [37,38], these should be supplied with treatment/care facilities to which the children could be referred. The following quote from an NGO representative demonstrates this: "Youths who come directly from war-affected areas need some kind of assistance.…”
Section: Lack Of Resourcesmentioning
confidence: 99%
“…This was illustrated by the findings on introducing child-friendly places, where human resources were a challenge. CFSs were presented as a psychosocial initiative, although other studies have found limited evidence for the effects of CFSs [37,38].…”
Section: Physical and Social Settingsmentioning
confidence: 99%